2015
DOI: 10.1055/s-0035-1547258
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heart Rate Variability and Cardiac Autonomic Nerve Remodeling in Streptozotocin-induced Diabetic Rats

Abstract: STZ-induced diabetes was associated with cardiac autonomic nerve dysfunction at both the organ and molecular levels. Parasympathetic nerves exhibited severe damage and/or weak recovery; remodeling of sympathetic nerves predominated during 10-weeks of STZ-induced diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
2
15
0
2
Order By: Relevance
“…Streptozotocin has been widely used for inducing diabetes mellitus in a variety of animals. STZ causes degeneration and necrosis of pancreatic β-cells [2][3][4][5]. Although the mechanism of the β-cell cytotoxic action of STZ is not fully understood, experimental evidence has demonstrated that some of its deleterious effects are attributable to induction of metabolic processes, which lead onto an increase in the generation of reactive oxygen species (ROS) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotocin has been widely used for inducing diabetes mellitus in a variety of animals. STZ causes degeneration and necrosis of pancreatic β-cells [2][3][4][5]. Although the mechanism of the β-cell cytotoxic action of STZ is not fully understood, experimental evidence has demonstrated that some of its deleterious effects are attributable to induction of metabolic processes, which lead onto an increase in the generation of reactive oxygen species (ROS) [6].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these results, it has been shown that kefir reduced pro-inflammatory cytokines, including TNFα, in DM [168,195]. The secondary outcomes included an improved lipid profile, blood pressure and hs-CRP, but kefir administration did not significantly change these parameters [191]. In contrast with experimental studies, it is still not clear whether kefir has beneficial effects on the lipid profile.…”
Section: Beneficial Effects Of Probiotics: Highlights Of Treatmentmentioning
confidence: 79%
“…For example, in the model of type 1 DM, an important imbalance of the cardiac autonomic nerves, located at both tissues and molecular pathways, has been observed. Recently, in the first 10 weeks of experimental DM, a marked cardiac dysfunction and an incomplete recovery of the cardioinhibitory vagal nerves, accompanied by a remodeling process in the stimulatory noradrenergic nerves [191], have been shown.…”
Section: Beneficial Effects Of Probiotics: Highlights Of Treatmentmentioning
confidence: 99%
“…Our results are consistent with those of studies showing the relatively early onset (at 3 weeks) of parasympathetic failure in STZ-induced diabetic rats. 25,26 In those studies, the mechanisms proposed to underlie autonomic neuropathy were depletion of cholinergic neurotransmitter vesicles in cardiac parasympathetic nerve endings 26 and autonomic nerve remodeling via the modulation of enzymes involved in neurotransmitter synthesis. 25 In our study, although there was no evaluation of the neuronal ultrastructural or biochemical changes, similar mechanisms are possibly taking place in the same type of diabetes model.…”
Section: Discussionmentioning
confidence: 99%